2021
DOI: 10.1002/ccr3.4411
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation in electrical hearing in a Morbus Meniere’s patient

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The phenomenon of fluctuating post-operative hearing in MD patients with prior ITG treatment shown in our study has already been reported by case reports [ 17 , 29 ]. The underlying mechanism for fluctuation in hearing in MD patients is still not clear.…”
Section: Discussionsupporting
confidence: 85%
“…The phenomenon of fluctuating post-operative hearing in MD patients with prior ITG treatment shown in our study has already been reported by case reports [ 17 , 29 ]. The underlying mechanism for fluctuation in hearing in MD patients is still not clear.…”
Section: Discussionsupporting
confidence: 85%
“…Fluctuations in speech understanding with CI are to be expected in patients with persistent auditory fluctuations because of active disease. Although longterm care outcomes for inactive Menière's disease have been described as good [21], active Menière's still requires considerable clinical or individual resources [22,23]. The impact on WRS 65 (CI) and subjective hearing-related impairment might be substantial [21,22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Although longterm care outcomes for inactive Menière's disease have been described as good [21], active Menière's still requires considerable clinical or individual resources [22,23]. The impact on WRS 65 (CI) and subjective hearing-related impairment might be substantial [21,22,24]. Previous studies have demonstrated that patients with active Menière's and fluctuating hearing have increased impedances and require continuous adjustments to the CI sound processor [25].…”
Section: Discussionmentioning
confidence: 99%